Plan de marketing para el posicionamiento de las cabañas la laguna en la ciudad de Latacunga provincia de Cotopaxi en el periodo 2014-2015 - Díaz Panchi, Lizbeth Maricela (2016)
The main objective of this research was to design a marketing plan to improve the positioning of Cabañas La Laguna. The lack of marketing strategies directly affect the positioning of the business which generates constraints on increasing sales levels, recruitment, retention and customer loyalty. This research involved an analysis of the current business situation, so first the same which is made by the breakdown of the dependent and independent variables that serve as reference for the development of this study the theoretical framework was developed. The methodology has a qualitative and quantitative approach, the applied methods are deductive and inductive because these helped to draw general conclusions from the research